Cooperative Enterprises in Australia and Italy Comparative analysis and theoretical insights - Jensen, Anthony; Patmore, Greg; Tortia, Ermanno (Strumenti per la didattica e la ricerca, 2015)
This book arises from a three-year comparative research program concerning co-operative enterprises in Australia and Italy. The book explores the historical development, legal framework and the peak organisations of co-operatives in the two countries. Specific comparative chapters focus on consumer, credit, and worker-producer co-operatives. The book deepens the analysis of co-operatives by containing chapters that examine specific theoretical and empirical issues such as the theory of co-operative firms as collective entrepreneurial action. Monographic chapters include more in depth analysis of specific typologies of co-operatives, such as social and community oriented co-operatives, some of which were created to contrast organized crime in Southern Italy. The book concludes with an assessment of the implications of the project for public policy.